Hydrodynamics of a high Alpine catchment characterized by four natural tracers - A. Michelon; N. Ceperley; H. Beria; J. Larsen; J. Larsen; T. Vennemann; B. Schaefli (Hydrology and Earth System Sciences, 2023)
Hydrological processes in high-elevation catchments are strongly influenced by alternating snow accumulation and melt in addition to summer rainfall. Although diverse water sources and flow paths that generate streamflow in the world's water towers emerge from these two driving inputs, a detailed process understanding remains poor. We measured a combination of natural tracers of water at a high frequency, including stable isotope compositions, electrical conductivity (EC), and water and soil temperature to characterize hydrological processes in a snow-dominated Alpine catchment and to understand the diversity of streamflow sources and flow paths. Stable isotope composition of the sampled water revealed the prominence of snowmelt year-round (even during winter baseflow), and a strong flushing of the entire system with snowmelt at the start of the main melt period, sometimes referred to as the freshet, led to a reset, or return to baseline, of the isotopic values in most sampled water. Soil temperature measurements help identify snow-free periods and indicate sub-snowpack local flow, for example, in the case of rain-on-snow events. Water temperature measurements in springs can indicate flow path depth. EC measurements reflect the magnitude of subsurface exchange and allow for the separation of subsurface snowmelt contribution to streamflow from the contribution of stored groundwater. These insights into the details of streamflow generation in such a dynamic environment were only made possible due to intense, year-round water sampling. The sampled tracers are revealed to complement each other in important ways particularly because they were sampled during winter and spring, both snow-covered periods, the importance of which is a key implication of this work.